PROTECTIVE PROPERTIES OF FLAVONOID EXTRACT OF COAGULATED TOFU (CURDLED SOY MILK) AGAINST ACETAMINOPHEN-INDUCED LIVER INJURY IN RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The total flavonoid contents of the various coagulated tofu and the hepatoprotective potential of all tofu flavonoid extracts were investigated. Tofu was prepared from locally sourced coagulants (steep water, alum, lemon, and lemon peel ash extract). Total flavonoid contents of all coagulated tofu were investigated as established in vitro flavonoid assay. The hepatoprotective activities of tofu flavonoid extracts against acetaminophen-induced hepatic cell toxicity in rats was also investigated in this study. The activity was analyzed by assessing the levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH). The concentrations of the serum sugar, total protein, albumin, and cholesterol as well as prothrombin time (PT) of experimental rats with histopathological analysis were also conducted. The range of the total flavonoid contents of tofu was 4.3-6.4 mg/g. Tofu flavonoid extracts significantly reduced the activities of serum AST, ALT, ALP, and LDH; total cholesterol, and sugar levels, but total protein and albumin concentrations increased compared to acetaminophen-intoxicated rats. Also, the prothrombin time prolongation of serum in acetaminophen intoxicated rats was reduced. Histology of the liver tissue demonstrated that tofu flavonoid extracts inhibited the acetaminophen-induced hepatic cell necrosis, decreased inflammatory cell infiltration and accelerated hepatocellular regeneration. Therefore, all tofus exhibited high total flavonoid contents, and the tofu supplement in human diets is highly recommended as it can be used as a functional food to prevent liver injuries.